2011
DOI: 10.4155/bio.11.118
|View full text |Cite
|
Sign up to set email alerts
|

The Six Critical Attributes of the Next Generation of Quality Management Software Systems

Abstract: Driven by both the need to meet regulatory requirements and a genuine desire to drive improved quality, quality management systems encompassing standard operating procedure, corrective and preventative actions and related processes have existed for many years, both in paper and electronic form. The impact of quality management systems on 'actual' quality, however, is often reported as far less than desired. A quality management software system that moves beyond formal forms-driven processes to include a true c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…38 A cross-sectional survey of 3.6 million patients' electronic records found that around 1% of the UK population may have diabetes (based on glucose blood test results) that is not recorded on practice registers, 1 and diabetes prevalence estimates based on Health Survey for England HbA1c measurements in 2006 suggested that up to 27% of diabetics were undiagnosed or missing from practice registers. 3 Variable use of complex coding systems may account for some of these missing patients, who may be less likely to receive well-organised care as a result. Mapping between systems has challenges, 39 though the automated linkage created within the Snoflake browser appeared reliable.…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…38 A cross-sectional survey of 3.6 million patients' electronic records found that around 1% of the UK population may have diabetes (based on glucose blood test results) that is not recorded on practice registers, 1 and diabetes prevalence estimates based on Health Survey for England HbA1c measurements in 2006 suggested that up to 27% of diabetics were undiagnosed or missing from practice registers. 3 Variable use of complex coding systems may account for some of these missing patients, who may be less likely to receive well-organised care as a result. Mapping between systems has challenges, 39 though the automated linkage created within the Snoflake browser appeared reliable.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…This is known as regulatory compliance and has been underpinned by better use of information systems. 3 The components of regulatory compliance, which also include the use of incentives and inspection, can be represented formulaically ( Figure 1). Clinical standards have been made explicit through a series of National Service Frameworks and a Cancer plan.…”
Section: Introductionmentioning
confidence: 99%